2006
DOI: 10.1158/0008-5472.can-05-2909
|View full text |Cite
|
Sign up to set email alerts
|

p130Cas as a New Regulator of Mammary Epithelial Cell Proliferation, Survival, and HER2-Neu Oncogene–Dependent Breast Tumorigenesis

Abstract: To investigate the mechanisms through which p130Cas adaptor protein is linked to tumorigenesis, we generated mouse mammary tumor virus (MMTV)-p130Cas mice overexpressing p130Cas in the mammary gland. MMTVp130Cas transgenic mice are characterized by extensive mammary epithelial hyperplasia during development and pregnancy and by delayed involution at the end of lactation. These phenotypes are associated with activation of Src kinase, extracellular signalregulated kinase 1/2, mitogen-activated protein kinase, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 41 publications
6
160
0
Order By: Relevance
“…Focal adhesions, the sites where the actin cytoskeleton is linked to the ECM by integrin/receptor complexes, contribute to cell anchorage and to the recruitment of signalling complexes that are involved in a broad range of cellular processes, including migration, proliferation, transformation and apoptosis. Remarkably, Src family kinases have been reported to act downstream of the modifications of the integrin/ ECM complexes that contribute to neoplastic transformation (O'Neill et al 2000, McLean et al 2003, Cabodi et al 2006. Although the role of adhesion molecules is also recognized in endocrine cancer cells (Ezzat & Asa 2005), no data are currently available in PETs.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesions, the sites where the actin cytoskeleton is linked to the ECM by integrin/receptor complexes, contribute to cell anchorage and to the recruitment of signalling complexes that are involved in a broad range of cellular processes, including migration, proliferation, transformation and apoptosis. Remarkably, Src family kinases have been reported to act downstream of the modifications of the integrin/ ECM complexes that contribute to neoplastic transformation (O'Neill et al 2000, McLean et al 2003, Cabodi et al 2006. Although the role of adhesion molecules is also recognized in endocrine cancer cells (Ezzat & Asa 2005), no data are currently available in PETs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, investigation of its expression in biopsies of different human malignancies using immunohistochemistry is still limited to breast cancer and haematological malignancies (Table I). Recently it has been reported that in human breast cancers overexpression of both ERBB2 and p130CAS is associated with increased proliferation, metastasis formation and poor prognosis 13,14 (Table I). Consistently, double transgenic mice overexpressing both p130CAS and ERBB2 in the mammary gland show an accelerated onset of tumour formation, providing evidence that p130CAS and the ERBB2 oncogene synergise in vivo to transform the mammary epithelium 13 (Table II).…”
Section: Integrin Adaptors In Cancermentioning
confidence: 99%
“…Recently it has been reported that in human breast cancers overexpression of both ERBB2 and p130CAS is associated with increased proliferation, metastasis formation and poor prognosis 13,14 (Table I). Consistently, double transgenic mice overexpressing both p130CAS and ERBB2 in the mammary gland show an accelerated onset of tumour formation, providing evidence that p130CAS and the ERBB2 oncogene synergise in vivo to transform the mammary epithelium 13 (Table II). Indeed p130CAS silencing in ERBB2 transformed breast cancer cells is sufficient to inhibit tumour growth in vivo, and correlates with downregulation of proliferative and survival pathways, such as SRC and AKT activation, focal adhesion kinase (FAK) phosphorylation and CYCLIN D1 expression 11 .…”
Section: Integrin Adaptors In Cancermentioning
confidence: 99%
“…High phospho-AKT and low AKT2 levels have been found associated with reduced survival of adjuvant tamoxifen-treated breast cancer patients [42]. We have demonstrated that BCAR1 protein levels are prognostic for disease recurrence and predictive for response to tamoxifen treatment [43][44][45], and BCAR1 also may be associated with HER2-Neu driven tumorigenesis [46,47]. GRB7 belongs to the 21 gene set (Oncotype DX assay) for breast cancer prognosis prediction and is often co-amplified with ERBB2 in breast cancer [9,29] and may contribute to the transformed cell phenotype [48].…”
Section: Bcar Genes and Progression Of Breast Cancermentioning
confidence: 99%